Simplifying the electronic wedge brake system model through model order reduction techniques - Che Hasan, Mohd Hanif; Hassan, Mohd Khair; Ahmad, Fauzi; Marhaban, Mohammad Hamiruce; Haris, Sharil Izwan; Arasteh, Ehsan (Institute of Advanced Engineering and Science, 2024)
The electronic wedge brake (EWB) uses self-reinforcement principles to optimise stopping power, but its mathematical model has various actuation angles and system dynamics making controller design complex and computationally burdensome. Therefore, the model order reduction (MOR) is made based on three factors that may have a negligible influence on the EWB system: the motor inductance, lead screw axial damping, and wedge mass. Six reduced order model (ROM) types were proposed when one, two, or all factors were ignored. The ROM accuracy was analysed using the frequency and time domain. The percentage of root means square error (RMSE) response value between the EWB benchmark model, and the predicted response based on the ROM was found to be less than 2%, with ROM size reduced from 5 to 2 orders. It guarantees that the new ROM series will be useful for simpler EWB controller design. The proposed ROM simplifies the original model drastically while retaining accuracy at an adequate level. Even though the simplest EWB model is a 2nd order linear system, the best ROM vary depending on EWB design parameters.